Trade, knowledge and networks: the activities of the Society of Apothecaries and its members in London, c.1670–c.1800. Issue 2 (14th June 2019) - SIMMONS, ANNA
Abstract: This article explores the activities of the Society of Apothecaries and its members following the foundation of a laboratory for manufacturing chemical medicines in 1672. In response to political pressures, the guild created an institutional framework for production which in time served its members both functionally and financially and established a physical site within which the endorsement of practical knowledge could take place. Demand from state and institutional customers for drugs produced under corporate oversight affirmed and supported the society's trading role, with chemical and pharmaceutical knowledge utilized to fulfil collective and individual goals. The society benefited from the mercantile interests, political connections and practical expertise of its members, with contributions to its trading activities part of a much wider participation in London's medical, scientific and commercial milieu. Yet, as apothecaries became increasingly engaged in the practice of medicine rather than the preparation and sale of drugs, the society struggled to reconcile the changing priorities of those it represented, and tensions emerged between its corporate and commercial activities.